Soil Contamination in One of Preschools Influenced by Metal Working Industry (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The aim of research was to estimate the present impact of drill plant or other pollution sources on soil anomalies of the preschool area and to reveal the depth of penetration of pollutants. Soil samples from 9 cores in the territory of the preschool were taken from 5 depth intervals: 0-0.5 m, 0.5-1.0 m, 1.0-1.5 m, 1.5-2.0 m and 2.0-3.0 m. Total number of samples was 45. Each sample was sieved to less then 2 mm fraction, milled and homogenised with binder before pressing 2 pellets. All pressed pellets were analysed by energy-dispersive x-ray fluorescence for determination of the contents of harmful chemical elements As, Ba, Cr, Cu, Mo, Ni, Pb, Sn, V, Zn and major elements Al, Ca, K, Fe, Mg, Na, P, S. Si, Ti. Samples where maximum permitted concentrations of Mo, Pb, Sn are exceeded occur not only in the uppermost layers, but also in the deeper layers. The highest median contents of most harmful chemical elements, except V and As, are in the uppermost 0.0-0.5 m layer and decrease with depth until 2.0-3.0 m or 1.5-2.0 m. To eliminate the influence of soil clay content in different samples, normalisation of concentration coefficients by the median of Al, K and Ti concentration coefficients was used. The depth of penetration is largely influenced by lithological composition of soil and is much deeper in sandy soil without layers enriched in clay.